Farmers’ Satisfaction with Dramatized Presentation Regarding Safe Use of Pesticides - Sahar, Bilal; Sharma, Anil Kumar; Gill, Jagjeet Singh (Indian Journal of Extension Education, 2020)
The present study was undertaken with the objectives to study reaction and satisfaction level of farmers with technical street play and gain in knowledge of the respondents. Five districts of Malwa region i.e. Ludhiana, Faridkot, Fazilka, Patiala and Mansa were selected purposively. From each district one village was selected and from each village thirty farmers were selected randomly to make a sample of 150 farmers. The data were collected by personal interview method with the help of questionnaire. Majority of the farmers gained information regarding harmful effect of pesticides on human health, harmful effect of pesticides on environment, seed treatment and safe use of pesticides etc. The socio-personal characteristics of the respondent were having significant association with their reaction towards street play on safe use of pesticide.
Keywords: Awareness; Dramatization; Pesticides; Reaction; Satisfaction